Acidentes com produtos perigosos no estado de Goiás evolução e causas - Oliveira, Wanderley Valério de (2011)
Accidents involving hazardous materials can have consequences that endanger the people present at the time of the accident, as much as the future generations. Incidents with these products are, in general, increasing all over the country and thus come the concern of knowing the main products involved in these accidents, the inherent risks and their causes. Therefore, in this work a compilation of accidents related to dangerous products in Goiás State in the 2007 2010 period was made to evaluate the risks and to correlate their possible causes. Data collection was done by raising the number of accidents related by the institutions that provide relief and those that scale the environmental impact, through informetrics and other literature such as reports, books and papers, to characterize the products involved in accidents and their potential risks. For this purpose, one counted on the support of 39 Military Fire Brigade from Goiás State quarters, from the dangerous products dealing companies, environmental enforcement and transit agencies, which also contributed to the assessment of the possible causes or correlations with the accidents. It was observed that most accidents was registered and answered by the Fire Brigade. The risks classes, such as gases, flammable liquids, corrosive, toxic and infectious substances showed the highest number of incidents and there was no occurrence with radioactive materials. The number of accidents increased every year and so the inclusion of vehicles, however, in most cases the dangerous product was stored. Hazardous materials with the highest number of occurrence in each year compiled were: liquefied petroleum gas, diesel oil, alcohol, gasoline and ammonia gas. The evolution of accidents comparison with the production amount, sales, inspections and installations allowed determining them possible causes. However, not always was possible to correlate the accident to a cause, and that may be due to a deficiency in the information technology of the service institutions, for example, just in 2009 the service system of the Fire Brigade was linked to the agencies of the Department of Public Safety, which increased the efficiency of the accidents record. Therefore, in 2007 and 2008 may have been large gaps on those records, due to the lack of information technology and, consequently, a lower realization of such accidents. Thus, one concludes that as more close to the reality the information on accidents become, more obvious becomes their causes, thus contributing to minimize the trouble.